The Effectiveness of Learning Sports through the Online Method on Kindergarten Students - Hanifan, Izzan; Sakti, Asri Wibawa (Jurnal Abdimas Kartika Wijayakusuma, 2021)
Online learning is a learning method by utilizing technology that allows direct interaction. With this activity, it is hoped that the effectiveness of learning sports through online methods can improve making it easier for educators and parents. Including sports learning at Harapan Bunda Kindergarten which is carried out online. The method in this study uses quantitative descriptive data collection techniques using questionnaires distributed via Google Form links. The results of this study indicate that: (1) student responses: (a) psychological complaints are: 70% bored and no complaints 30%, (b) understanding of sports learning materials: 50% easy to understand, 50% do not understand, (c ) the benefits of physical exercise learning: 70% felt and 30% did not feel, (d) Learning effectiveness: 40% said it was effective and 60% said it was not effective, (2) facilities and infrastructure: (a) the type of internet connection used by students: 70% use quota and 30% use WiFi, (b) problems while online: 60% say limited quota and 40% say network is unstable, (c) applications that are easy to use while online: 90% say whatsapp and 10% say zoom meeting, (3) student activities: (a) attitude when the teacher explains the material: 100% pays attention, (b) readiness to take part in online sports learning: 80% says ready and 20% says not ready, (c) attendance: 90% attends and 10% absent. Therefore, referring to engagement results from indicators of student activity, attitude, attendance, and readiness to learn shows high results, the effectiveness of online sports learning can be increased through infrastructure and the use of applications that are easy to use during the learning process.